COVID-19 and the promise of food system innovation - Hawkes, Corinna (International Food Policy Research Institute, 2020)
One of the silver linings of any crisis is the innovation it produces. And when it comes to food, COVID-19 is no exception. The evidence, anecdotal as it is, shows that lockdowns around the world have had a profound impact on the markets, transport, and labor supply needed to produce, distribute, and sell nutritious foods. With reports of vegetables rotting in the fields and milk being thrown away while people go without, a clear mismatch has emerged between supply and demand. But as things have closed down, new spaces have opened up. Innovations driven by government, business, and communities targeting production, distribution, markets, and consumers have proliferated to enable food to get to people who need it in new ways. Crisis often necessitates new actions for short-term solutions. But given the longer-term problem of undernutrition and overweight around the world, and the ongoing conversation about how food systems need to change, it’s worth asking: do these innovations tell us anything about what is possible and beneficial for food systems transformation toward nutritious, healthy diets for all?